Linking the trust of industrial entrepreneurs on elements of ecosystem with entrepreneurial success: Determining startup behavior as mediator and entrepreneurial strategy as moderator - Rehman, Zia Ur; Arif, Muhammad; Gul, Habib; Raza, Jamshed (Frontiers in Psychology, 2022)
to examine the link between entrepreneurs social capital (trust on three elements of ecosystem i.e., trust on experts & enterprises, trust on media, trust on government) and entrepreneurial success (both individual and firm success). Specifically, this study analyzed entrepreneurs dispositional factor (startup behavior) as underlying mechanism between trust and entrepreneurial success. Furthermore, this study also analyzed entrepreneurs situational factor (entrepreneurial strategy) as boundary condition. Design/methodology/approach – We applied time-lagged data collection from 505 owners and top executives of manufacturing industry in Pakistan. Findings – The direct impact of trust on three elements of ecosystem is found significantly positive on both startup behavior and entrepreneurial success. The direct impact of startup behavior on entrepreneurial success is significantly positive. The indirect mediation impact of startup behavior is positively significant between trust and entrepreneurial success. The moderated and moderated mediation impact of entrepreneurial strategy is found positively significant at low and medium values. But this study found insignificant moderated impact at high values of entrepreneurial strategy between trust on media and startup behavior. Furthermore, this study also found insignificant moderated mediation impact at high values of entrepreneurial strategy by interacting with two elements of ecosystem (trust on media and trust on Government) through startup behavior on entrepreneurial success. Originality/value –Authors suggested that startup behavior is underlying mechanism through which entrepreneurs trust influenced entrepreneurial success. The authors also suggested as to when trust matters more in predicting entrepreneurial success at low or high entrepreneurial strategy. Implications – This study contributed to literature on entrepreneurial strategy for its conditional indirect moderated impact on startup behavior and moderated mediation impact on firm entrepreneurial success. This study also contributed to owners of manufacturing industry for their startup behavior as underlying mechanism through which trust influence entrepreneurial success.